Analisis Deskriptif Motivasi Kerja Pegawai: Studi Pada Salah Satu Instansi Pemda di Kota Cimahi - Mia Nursanty; M Sidik Priadana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2020)
Work motivation can be a driving force for someone to carry out an activity to get the best results; there needs to be a solid push to increase individual motivation. Departing from the critical role of work motivation, the researcher intends to research employee work motivation. The goal is to get an overview of employee work motivation at one of the local government agencies in Cimahi City. Based on the aims and objectives of the study, the researcher used a descriptive approach to describe employees' work motivation. Respondents who are uses as samples are employees who one of the local government agencies as many as 114 employees. The results of the study illustrate that the study resultss' work motivation is in the good enough to good category. The study results indicate that the condition of employee motivation is adequate; however, it needs to be improved by the leadership of the local agency to achieve optimal employee motivation.